2001
DOI: 10.1159/000047438
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Three Minimal Intervention Approaches for Managing Dental Caries: Survival of Restorations after 2 Years

Abstract: The present study was aimed at comparing the effectiveness of three minimally invasive restorative treatment approaches for dentinal lesions in occlusal surfaces. The approaches tested comprised a conventional and a modified–conventional treatment and a modified Atraumatic Restorative Treatment (ART). The conventional approach was performed in a university dental clinic whilst the modified–conventional, employing portable equipment, and the modified ART, using hand instruments and a caries removal solution (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 8 publications
2
33
0
1
Order By: Relevance
“…period. This is in agreement with the results of other studies in Zimbabwe [Frencken et al, 1998a, b], in Tanzania [Mandari et al, 2001] and in China [Holmgren et al, 2000]. The 12-month success rates of the class I ART restorations placed in the primary teeth in this study were also very high, being over 90%.…”
Section: Discussionsupporting
confidence: 93%
“…period. This is in agreement with the results of other studies in Zimbabwe [Frencken et al, 1998a, b], in Tanzania [Mandari et al, 2001] and in China [Holmgren et al, 2000]. The 12-month success rates of the class I ART restorations placed in the primary teeth in this study were also very high, being over 90%.…”
Section: Discussionsupporting
confidence: 93%
“…The early results of the ART studies have been promising, but improvements in performance and longevity of fillings are still being sought. In a later study, Mandari et al [10] not find a statistically significant difference between onesurface amalgam and glass ionomer fillings after 2 years.…”
Section: Introductionmentioning
confidence: 80%
“…However, many ART studies [4][5][6][7][8][9][10]17] have confirmed the advantages of this technique and successful performance of restorations in class I cavities. The test glass ionomer filling was manufactured as a universal glass ionomer filling material also indicated for use with the ART approach.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical success rate of the ART approach is fairly high in initial, short-term studies. [9][10] However, no long-term studies are available yet, and few studies have been done on the bond strength and microscopic characteristics of the bonding interface between GICs and carious dentin.…”
Section: Introductionmentioning
confidence: 99%